Sosialisasi Membangun Generasi Tangguh Melawan Kejahatan Cyber pada SMK Plus Krida Utama Padalarang - Ade Yuliana; Novita Lestari Anggreini; Castaka Agus Sugianto; Heldi Akbar Kosasih (Yayasan Pemimpin Inovasi Science, 2025)
This community service program aims to improve digital literacy and cybersecurity awareness among vocational high school students at SMK Plus Krida Utama Padalarang. The increasing threat of cybercrimes such as phishing, hacking, malware, and cyberbullying poses significant risks to students who are often active but underprepared digital users. Through interactive workshops, real-life case studies, and quizzes, the program successfully enhanced students’ understanding of cyber threats and prevention strategies. The sessions focused on practical steps like using strong passwords, recognizing suspicious links, managing online privacy, and practicing safe digital behavior. Evaluation results indicated increased student engagement and awareness, demonstrating the importance of early cybersecurity education. The outcomes suggest that structured and relatable digital safety training is effective in building resilience against cybercrime among young users.